Parental and early-feeding effects of dietary methionine in rainbow trout (Oncorhynchus mykiss) - Fontagne-Dicharry, Stephanie (2019)
We studied the effect of changes in dietary methionine (Met) supply in broodstock and first-feeding rainbow trout fry (offspring). Three plant-based diets differing in Met level (deficient, adequate or in excess of the established requirement) were fed to the broodstock (male and female) for 6 months prior to spawning (diets BD, BA and BE, respectively). The offspring from the parental Met-groups was then challenged in turn with the different Met fry-diets (FD, FA and FE, respectively) for 3 weeks from first-feeding. At spawning, females fed diet BD had significantly higher plasma total and LDL-cholesterol and slightly lower plasma triacylglycerol. Diet BD reduced female (but not male) growth, weight of spawn and egg size, but had no effect on relative fecundity. The free amino acid profile of oocytes was modified, with levels of Met and Cys correlating positively with the Met-levels of broodstock diets. SAM and SAH levels in oocytes followed the same pattern, as opposed to SAM/SAH ratio. At the swim-up stage, no significant effect of parental diet on fry weight was noted, whereas survival was the highest in fry from BE-broodstock. The subsequent 21-day fry feeding with different Met levels highly affected the daily growth index with a significant interaction between the parental-diet and fry-diet effects. The expression of a number of genes regulating sulfur amino acid metabolism was modified either directly by the dietary Met supply in both broodstock liver and in whole fry (e.g. BHMT1, GR, GST pi, MsrA1) or indirectly by the parental Met intakes as seen in the swim-up fry (e.g. BHMT1, MTR, GST pi, MsrA1). Importantly, long-lasting parental effects linked to broodstock Met-intake were seen in the fry, 21-days after first-feeding and irrespective of the fry diet (CTH, MsrA1, MsrB2, SOD2). Similarly, parental effects were noted on the gene expression of both NPY and POMC feeding peptides in fry prior to exogenous feeding which persisted for POMC in the 21-day fry. Parental effects were also demonstrated on the key myogenic gene Myog, on fMHC and GDH in swim-up fry, which persisted for GDH in 21-day fry. In summary, our results demonstrate that dietary Met levels of rainbow trout broodstock affect various traits in the offspring, some of which persisted during the first weeks of exogenous feeding. Further studies need to evaluate the long-term persistence of the parental effects over time and to elucidate the mechanisms, whether epigenetic or not. Statement of relevance: Determining the multiple effects of dietary methionine levels on reproductive, growth performance and metabolism in offspring will help improve formulations of low fish meal feeds for rainbow trout at sensitive life cycle stages. (C) 2016 Elsevier B.V. All rights reserved.